Empirical Evidence on Economic Profit in Telecoms: the Case of Emerging Markets - Ирина Васильевна Ивашковская; М. В. Слободина (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
The article reports empirical evidence on the relationship of economic profit and market value creation in 41 telecoms from BRIC, Central and Eastern European economies. We study residual income as well as economic value added with the adjustments to invested capital. We show that economic profit performance measures have high explanatory power. On the contrary accounting rates of return are not statistically significant in the sample.